The Effect of Example Non-Example Teaching Model on Tenth Grade Students' in Writing Descriptive Text of SMA Negeri 2 Pematangsiantar - Leta Denarosana Rumahorbo; Leonita Maria Efipanias Manihuruk; bas Lolo Siahaan (The Future of Education Journal, 2024)
This study was conducted to determine the effect of the Example Non-Example Teaching Model on the ability of tenth grade students in writing descriptive texts at SMA Negeri 2 Pematangsiantar. The theory used in this research is theory. The research methodology used in this research is quantitative method using quasi-experimental research design. The population of this study was tenth grade students of SMA Negeri 2 Pematangsiantar in the 2024/2025 school year. Researchers took two classes as samples. The samples taken were class X-3 as an experimental class consisting of 36 students and class X-4 as a control class consisting of 36 students. The experimental class was taught with the Example Non-Example learning model, while the control class was taught with the conventional model. Data was obtained using pre-test and post-test given to both groups. The mean value of the experimental class in the pre-test was and the mean value of the control class was. On the other hand, the average variable in the experimental class on the post-test was, while the average score of the control class on the post-test was. To obtain the data, the researcher used a test as an instrument. The t-test results show that the calculated t value is greater than the t table at the 5% significance level (1.666). The significance value results show that the alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected. This means that there is a significant effect of using the Example Non-Example learning model on tenth grade students of SMA Negeri 2 Pematangsiantar in writing descriptive text.